(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This study investigates the medicinal properties of teas prepared from peach (Prunus persica), hibiscus (Hibiscus sabdariffa), and quince (Cydonia oblonga) leaves, focusing on their antioxidant, anti-inflammatory, and metabolic regulatory effects. Laboratory experiments were conducted to quantify bioactive compounds, assess antioxidant capacity, and evaluate their impact on cellular models. Results indicate significant antioxidant activity in all three teas, with hibiscus exhibiting the highest anthocyanin content and quince leaf tea showing notable hypoglycemic effects. These findings suggest potential therapeutic applications for managing oxidative stress, inflammation, and metabolic disorders. The study provides a comprehensive analysis of preparation methods, chemical composition, and biological activity, contributing to the growing body of evidence supporting the use of plant-based teas in preventive healthcare.